Pharmacokinetic and Pharmacodynamic integration of tilmicosin against Mycoplasma gallisepticum in the target infection site in chickens - Zhang, Nan; Zhou, Minghu; Yan, Xiu; Liu, Jinxin; Yuan, Sheng; Yang, Hong; Ding, Huanzhong; Zhang, Dexian; Bai, Yinshan (Frontiers in Veterinary Science, 2022)
Mycoplasma gallisepticum (M. gallisepticum) is a primary respiratory pathogen of poultry and causes significant economic losses to the poultry industry. There were no reported articles concerning the Pharmacokinetics/Pharmacodynamics (PK/PD) interactions of tilmicosin against M. gallisepticum in vivo. In the current study, we established an in vivo M. gallisepticum infection model and tilmicosin was administered orally to the M. gallisepticum infected chickens by different dosage regimens. The concentration of tilmicosin in lung tissue was determined by HPLC-MS/MS (High pressure liquid chromatography/tandem mass spectrometry), besides the counting of the viable colony of M. gallisepticum in lung tissue was also monitored dynamically to appraise the PK/PD interactions of tilmicosin against M. gallisepticum. We found that anti-mycoplasmal activity was concentration dependent and mycoplasmacidal activity was observed at tilmicosin dosage > 7.5 mg/kg. The PK/PD parameter of AUC/MIC (The area under the concentration-time curve divided by the MIC) correlated well with anti-mycoplasmal efficacy (R2 = 0.92). The ratios of AUC/MIC for 1 log10 and 3 log10 CFU/lung reductions were 300.02 and 6950.15 h, respectively. These findings indicated that tilmicosin may be therapeutically effective in chickens to treat M. gallisepticum lung infections if administered at a dose of 9.12 mg/kg.